Reinforcement of students’ Higher Order Thinking Skills through project based learning with scaffolding - Jamaluddin, Nor Sa’adah; Abd Kadir, Suhaida; Abdullah, Arnida; Alias, Siti Noormi (Human Resource Management Academic Research Society, 2019)
Higher Order Thinking Skills is one of the six students’ aspirations that focus on the education ‘Blueprint’ or Malaysia Educational Development Plan (MEDP) 2013-2025. Producing students that have good and successful mastery level of HOTS could prepare the students in competing at global education scene aside from creating students with high marketability value. A good and successful mastery of HOTS is related to Teaching and Learning strategy that is utilized by teachers in schools. Choosing the correct and suitable Teaching and Learning strategy could transform the students’ mind to think creatively, critically, and innovatively in completing a task or solving a problem. Application of Project Based Learning (PBL) is one of the common Teaching and Learning strategy that is emphasized in schools. A research is carried out towards Form 4 Accounting students in studying the effect of PBL towards mastery of HOTS precisely in topic ‘cash budget’ with the involvement of scaffolding element. The research uses quasi-experimental method that includes one experimental group participating in pre-test and post-test. Computerized statistical software “IBM SPSS Statistics” version 22 is utilized for the purpose of data analysis. Results from paired t-test show that there is a significant difference between the mean of the students’ mastery level of HOTS in pre-test and post-test that involves PBL with scaffolding. Therefore, the involvement of scaffolding element in PBL contributes towards increase in students’ mastery of HOTS and proofed that PBL is suitable to be implemented in Teaching and Learning session in schools.